Romanian Agri-Food Businesses and the European Green Deal: An Exploratory Approach - Călin Vegheș; Andreea Strâmbu-Dima (Amfiteatru Economic)
The increase of the concentration of greenhouse gases and global warming are the main problems that the European Commission is trying to solve by proposing the Green Deal, but the well-being of agri-food businesses is influenced, next to the ecologic factors, by the social and economic factors such as maintaining competitive pricing, especially when competing with agri-food businesses that are not affected by the European sustainability measures, and consumers’ interest in buying sustainable products. Analysing the current state of knowledge and carrying out a qualitative exploratory research among the agri-food organizations in Romania, the coordinates of the Romanian agri-food market and a series of its peculiarities were outlined. The research results show that there is a positive perception regarding the opportunity to implement the Green Deal’s measures and suggest using a strategic matrix to facilitate their adoption in the context of current economic and social transformations.